Boardwalk bust - Dixon, Franklin W. (New York : Aladdin Paperbacks, 2005)
Frank and Joe travel to New Jersey where they investigate a series of robberies at jewelry stores. In Boardwalk Bust, Frank and Joe head to Ocean Grove, New Jersey, to investigate a rash of jewelry store robberies. The temperature's sizzling; will the boys be able to smoke out 'sticky fingers' before they're burned? Mission: Investigate and put a halt to the recent rash of jewelry store robberies. Potential danger on the ground and in the air. Location: Ocean Grove, NJ. Potential victims: All jewelry store owners in and around Ocean Grove. Suspects: Undetermined. Ocean Grove is full of tourists who are just passing through. This mission requires your immediate attention. This message will be erased in five seconds.
008-012.
Keywords: Hardy Boys (Fictitious characters) -- Juvenile fiction; Robbery -- New Jersey -- Juvenile fiction; Jewelry stores -- Juvenile fiction; Stores, Retail -- Juvenile fiction; Detective and mystery stories -- Juvenile fiction; New Jersey -- Juvenile fiction